Ambient Intervention dalam Wellness Cafe Studi Kasus : Clear Cafe Ubud: Studi Kasus Clear Cafe Ubud - Utami, Ni Kadek Yuni (Waca Cipta Ruang, 2022)
The purpose of this study is to explore how the interior of a cafe as a place for body mind and spirit (wellness). This article describes how the balance is occurs with the interior-ambient intervention, through light, sound, odor, and temperature. The method used is quantitative where the researcher will conduct a questionnaire on the perception of Wellness in the interior and the experience of visitors at Clear Cafe Ubud which is one of the cafes that carries the concept of wellness in Ubud. In addition, Clear Cafe Ubud interior data was taken from the internet to determine the application of the elements of light, sound, odor and temperature on the interior is correlated with the responden’s needs and experiences. The findings in this study are that the success of the cafe as a wellness space is influenced by ambient intervention in the interior. This finding also shows that the balance of body, mind and spirit is generated from interior elements that provide tranquility, intimacy, and relaxation in harmony with the principle of natural balance. This study may give a direction to the designer or manager cafe in determining the development of cafe interior design as a wellness space. Keywords: interior design, wellness cafe, ambient intervention